2018
DOI: 10.1021/acs.cgd.8b00995
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Mefenamic Acid Nucleation by a Surfactant Additive, Docusate Sodium

Abstract: The influence of docusate sodium (DOSS) on the nucleation of mefenamic acid (MEF) has been studied in different dimethylacetamide (DMA)-water mixtures. A series of induction time experiments were conducted under moderate supersaturations, varying the solvent composition and the concentration of DOSS. In 40 % DMA-60 % water, the presence of 0.1 mg/mL and 0.2 mg/mL DOSS increased the nucleation rate. Evaluating the results by the classical nucleation theory reveals that the pre-exponential factor (A) increases b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…14,42 Similar results were obtained by Heffernan et al, 64 where the presence of structurally similar impurities (demethoxycurcumin (DMC) and bisdemethoxycurcumin (BDMC)) in the curcumin solution did not inuence the interfacial energy of the crystallising solute, but instead changed the pre-exponential factor. 64 Another report by Bodnár et al 65 also presents similar ndings, where the presence of docusate sodium (DOSS) in a mefenamic acid solution in dimethylacetamide (DMA)-water mixtures resulted in an approximately 50% increase in the pre-exponential factor, while the interfacial energy remained uninuenced. Hence, the nucleation of organics in the presence of heterosurfaces in either a dissolved or undissolved state is inuenced by the change in the pre-exponential factor, while the interfacial energy remains uninuential.…”
Section: Papermentioning
confidence: 69%
“…14,42 Similar results were obtained by Heffernan et al, 64 where the presence of structurally similar impurities (demethoxycurcumin (DMC) and bisdemethoxycurcumin (BDMC)) in the curcumin solution did not inuence the interfacial energy of the crystallising solute, but instead changed the pre-exponential factor. 64 Another report by Bodnár et al 65 also presents similar ndings, where the presence of docusate sodium (DOSS) in a mefenamic acid solution in dimethylacetamide (DMA)-water mixtures resulted in an approximately 50% increase in the pre-exponential factor, while the interfacial energy remained uninuenced. Hence, the nucleation of organics in the presence of heterosurfaces in either a dissolved or undissolved state is inuenced by the change in the pre-exponential factor, while the interfacial energy remains uninuential.…”
Section: Papermentioning
confidence: 69%
“…As discussed in a previous study, the Zeldovich factor z depends on the supersaturation ratio, Boltzmann constant, temperature, molecular volume in the crystal, and the interfacial energy, and these values are unlikely to change due to the presence of impurities . Instead, impurities may interact with nucleation interfaces, effectively lowering the concentration of nucleation sites C 0 for PA.…”
Section: Resultsmentioning
confidence: 81%
“…Consequently, the solubility of the product may decrease due to the presence of common ions or increase as a result of complex formation or the presence of foreign ions . Impurities furthermore may influence the nucleation process by changing the solid–liquid interfacial energy and/or the kinetic factor, or they may act as heterogeneous surfaces. , For instance, amphiphilic, polymeric, and surfactant additives were found to promote nucleation. In other studies, it was found that additives and impurities did not significantly influence the interfacial energy but instead led to a reduction in the kinetics. , These findings were explained using the additional energy that is required to remove the impurity from the clustering process. Finally, additives can be used to influence the processability of pharmaceutical compounds by changing the intrinsic physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 presents the influence of solvent on these parameters for tolbutamide, 36 salicylic acid, 37 and risperidone 38 which clearly show a solvent effect in determining the values of the preexponential factors and interfacial energies. Two studies on curcumin 39 and 3-nitrophenol 40 demonstrate the effects of impurities on the pre-exponential factors and interfacial energies and finally there are 4 studies which show how these factors change for polymorph pairs, namely eflucimibe, 11 D-mannitol, 12 mefenamic acid, 41 and famotidine. 13 Perusals of the data in Table 1 indicated that ratio of preexponential factors for the various crystallizations encountered rarely exceed 10 3 .…”
Section: Introductionmentioning
confidence: 99%